Patients’ awareness of their rights, associated factors and its practice by health professionals from a patient perspective among elective surgical patients at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: a cross-sectional study, 2021 - Kaletsidk Dessalegn; Betelihem Girma; Keder Essa Oumer; Metages Hunie; Kumlachew Geta Belete (BMJ Open)
Objectives To assess the patients’ awareness of their rights, associated factors and the practice of these rights by the medical team from the patients’ perspective at Tikur Anbessa Specialized Hospital.DesignAn institution-based prospective cross-sectional study was carried out.Setting The research was conducted from January to May 2021 in a specialised hospital in central Ethiopia.Participants 392 people who had elective surgery were included in this study; 217 men and 175 women responded. Systematic random sampling was employed to choose the research subjects, and K (skip interval) was calculated using the 3-month surgical waiting list at the hospital. Patients under the age of 18, those with severe illnesses, those who were not inpatients, and those who had diagnosable mental conditions were not eligible.Primary and secondary outcome measures A structured questionnaire was administered in a face-to-face interview by trained data collectors after surgery at the surgical ward and analysed by using SPSS V.24. Bivariate and multivariable regression analyses were used to identify the associated factors. A p<0.05 was used to judge the significance of the association.Result Patients’ awareness about their rights was 76%. Educational level, place of residency and the number of hospital admission were significantly associated with patients’ awareness. The majority (83.2%) of patients reported that health providers had poor practices regarding patient rights.Conclusion Most patients were unaware of most of their rights, and the majority of patients reported that healthcare providers did a poor job of protecting their patients’ rights. To advance the application and understanding of patient rights, access to various facilities, patient and healthcare provider education programmes, and patient rights information technology must be improved.